Adverse events following administration of COVID-19 vaccines in Saudi Arabia - Saleh Alqahtani; Hani Jokhdar; Jaffar A. Al-Tawfiq; Salah Al-Otaibi; Abdullah Assiri; Sami Almudarra; Khaled Alabdulkareem; Alhan Haji (Scientific Reports, 2022)
Abstract Previous studies investigated the frequency of different adverse events of COVID-19 vaccines. However, this study compares these adverse events between the two main COVID-19 vaccines used in Saudi Arabia (Pfizer-BioNTech and Oxford-AstraZeneca) using telemedicine technology. A cross-sectional study was conducted among 958 individuals, 7 days after receiving either Pfizer-BioNTech or Oxford-AstraZeneca vaccines during June 2021. Immediate adverse events were reported by 1.04% and 2.09% for Pfizer-BioNTech and Oxford-AstraZeneca vaccines, respectively, with no serious events. Recipients of Pfizer-BioNTech vaccine had a higher percentage of local adverse events (24.8% versus 9.8% in AstraZeneca vaccine). The most common reported systemic adverse events in both vaccines respectively were general fatigue (23.1% and 25.1%), fever (18.5% and 27.2%), myalgia (20.6% and 20.3%), and headache (15.2% and 17.2%). No significant difference was recorded between both vaccines regarding overall systemic adverse events; however, they were more frequent following the first dose of AstraZeneca vaccine compared to Pfizer-BioNTech vaccine, while the reverse was observed for the second dose. Adverse events were more frequent in females and younger age groups for both vaccines. Most of systemic and local adverse events were mild in nature. Further cohort studies are recommended to investigate the long-term adverse events of COVID-19 vaccines.